Wage Determination in the Shadow of the Law: The Case of Works Councilors in Germany - Laszlo Goerke; Markus Pannenberg (Institute of Labor Economics (IZA), 2021)
The German law on co-determination at the plant level (Betriebsverfassungsgesetz) stipulates that works councilors are neither to be financially rewarded nor penalized for their activities. This regulation contrasts with publicized instances of excessive payments. The divergence has sparked a debate about the need to reform the law. This paper provides representative evidence on wage payments to works councilors for the period 2001 to 2015. We find wage premia of 2% to 6% in OLS-specifications, which are more pronounced for long-term works councilors. Moreover, we observe no wage premia in linear fixed-effects panel data specifications, suggesting that the OLS-results capture the effect of selection into works councillorship. We obtain no evidence for a delayed compensation or a special treatment of works councilors released from work. Hence, our results indicate that payments to works councilors are broadly in line with legal regulations.
Keywords: J30; J51; J53; J83; K31; 330; labor law; wages; works councils; socio-economic panel (SOEP)